2010
DOI: 10.1007/s00425-010-1129-6
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the roles of desiccation-induced xanthophyll cycle activity in darkness: a case study in Lobaria pulmonaria

Abstract: Desiccation-tolerance ability in photosynthetic organisms is largely based on a battery of photoprotective mechanisms. Xanthophyll cycle operation induced by desiccation in the absence of light has been previously proven in the desiccation-tolerant fern Ceterach officinarum. To understand the physiological function of xanthophyll cycle induction in darkness and its implication in the desiccation tolerance in more detail, we studied its triggering factors and its photochemical effects in the lichen Lobaria pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 41 publications
4
38
0
1
Order By: Relevance
“…This idea is supported by the fact that it is a common response to dehydration in all desiccation-tolerant species belonging to different lineages analysed so far (Fig. 1b, d, f, h, j, l) (see also Fernandez-Marin et al 2010).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This idea is supported by the fact that it is a common response to dehydration in all desiccation-tolerant species belonging to different lineages analysed so far (Fig. 1b, d, f, h, j, l) (see also Fernandez-Marin et al 2010).…”
Section: Discussionsupporting
confidence: 57%
“…(Fernandez-Marin et al 2010). Although Z formation has also been reported in dehydrating leaf discs of several vascular plants (Fernández-Marín et al 2009), the extent of this trait across the plant kingdom and its relationship to desiccation tolerance are unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Such increase relates to J and I chlorophyll fluorescence levels that are attributed to energy transfer from LHCs to RCs and a primary acceptor. Similar results were obtained for DTTtreated algal lichen Lobaria pulmonaria by Fernández-Marín et al (2010) who reported DTT-induced increase in I and J chlorophyll fluorescence level in dried and subsequently hydrated thalli. Their explanation of the chlorophyll fluorescence increase relates to an integrity and function of the photosynthetic apparatus during desiccation and a potential role of lack zeaxanthin in this process.…”
Section: Dtt Effectssupporting
confidence: 88%
“…This mechanism has already been demonstrated in the lichen Lobaria pulmonaria (L.) Hoffm. [86], and could explain declines in lichen cover with warming, as desiccation should occur much faster because of the temperature increase in this treatment (see the electronic supplementary material, appendix S5). Mosses usually show more structural complexity than lichens [83,87], and this may allow mosses to have quicker responses to desiccation [88].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, recent studies [85,86] suggest that if desiccation occurs faster than in normal conditions, photoprotective mechanisms do not work properly, and, as a consequence, structural damages are likely to occur. This mechanism has already been demonstrated in the lichen Lobaria pulmonaria (L.) Hoffm.…”
Section: Discussionmentioning
confidence: 99%